1998
DOI: 10.1046/j.1432-1327.1998.2550698.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of amino acid aryl amides by the intestinal H+/peptide cotransport system, PEPT1

Abstract: Transport of amino acid aryl amides by the intestinal H ϩ /peptide symporter (PEPT1) was studied in Caco-2 cells and in Xenopus laevis oocytes expressing human PEPT1. Several amino acid amides were able to inhibit the uptake of [ 14 C]glycylsarcosine in Caco-2 cells. Ala-4-nitroanilide (K i ϭ 0.08 mM), Phe-4-nitroanilide (K i ϭ 0.09 mM) and Ala-4-phenylanilide (Ki ϭ 0.03 mM) were accepted as substrates with equal or higher affinity than natural Ala-Xaa dipeptides. Ala-anilide (K i ϭ 2.9 mM), Ala-7-amido-4-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…Large sets of dipeptides, amino acid derivatives, or peptidomimetics have been probed for transport in competition experiments utilizing cells expressing either one of the transporters, by the measurement of substrate-mediated transport currents in Xenopus laevis oocytes expressing PEPT1 or PEPT2, or by competition experiments in the yeast Pichia pastoris heterologously expressing either one of the mammalian transporters (11,12,14,21,22,66,67). One important finding for understanding the "multispecificity" of the peptide transporters was that neither PEPT1 nor PEPT2 requires a peptide bond in a substrate and that the minimal structural requirement in a substrate for binding and transport is a simple carbon chain that separates the oppositely charged NH 2 and COOH head groups by an intramolecular distance of Ͼ 500 Ͻ 630 picometers (21).…”
Section: The Substrate Specificity Of Pept1 and Pept2mentioning
confidence: 99%
“…Large sets of dipeptides, amino acid derivatives, or peptidomimetics have been probed for transport in competition experiments utilizing cells expressing either one of the transporters, by the measurement of substrate-mediated transport currents in Xenopus laevis oocytes expressing PEPT1 or PEPT2, or by competition experiments in the yeast Pichia pastoris heterologously expressing either one of the mammalian transporters (11,12,14,21,22,66,67). One important finding for understanding the "multispecificity" of the peptide transporters was that neither PEPT1 nor PEPT2 requires a peptide bond in a substrate and that the minimal structural requirement in a substrate for binding and transport is a simple carbon chain that separates the oppositely charged NH 2 and COOH head groups by an intramolecular distance of Ͼ 500 Ͻ 630 picometers (21).…”
Section: The Substrate Specificity Of Pept1 and Pept2mentioning
confidence: 99%
“…The intestinal peptide transporter PEPT1, belonging to the same family as PEPT2, mediates the uptake of di-and tripeptides and derivatives into intestinal epithelial cells in a similar mode. PEPT1 has been studied extensively with respect to substrate specificity, and findings allowed the formulation of preliminary predictive models for substrate recognition (Borner et al, 1998;Brandsch et al, 1998Brandsch et al, , 1999Döring et al, 1998d;Meredith et al, 1998). In previous studies (Döring et al, 1998d), we showed that PEPT1 transports -amino fatty acids electrogenically with affinities that are similar to those of native dipeptides.…”
mentioning
confidence: 87%
“…Recent findings demonstrated that amino acid arylamides completely lacking a terminal carboxylic group serve as substrates for PEPT1 (Borner et al, 1998). To probe whether this also applies to PEPT2, we used a set of para-substituted alanine-anilides having the structures provided in Fig.…”
Section: Structure-activity Relationship Of Peptide Transporter Pept2mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Enhanced bioavailabilities of the amino acid prodrugs is attributed to carrier mediated intestinal absorption via intestinal transporters such as a human peptide transporter hPept1 or an amino acid transporter ATB 0,ϩ . 4,[10][11][12] Nucleoside antiviral and anticancer agents are important class of drugs for the fight against viral diseases and cancer. However, they often exhibit poor pharmaceutical and absorption, distribution, metabolism and excretion (ADME) properties.…”
mentioning
confidence: 99%